2021
DOI: 10.26905/afr.v3i2.5503
|View full text |Cite
|
Sign up to set email alerts
|

Pengelolaan Keuangan Daerah dan Good Governance terhadap Kinerja Satuan Kerja Perangkat Daerah

Abstract: This study aims to describe regional financial management which includes: planning and budgeting, implementation and administration and accountability of regional finances; and transparency which includes transparency and accessibility; as well as the accounta-bility of regional financial reporting, the effectiveness of internal and external party super-vision, and the performance of Regional Work Units; analyze the effect of the effectiveness of financial planning, the effectiveness of budget execution contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
2
0
4
Order By: Relevance
“…Based on the test results, these findings are relevant to the study of [2] shows that the Special Allocation Fund has a positive and significant effect on the level of regional financial independence. This shows that the realization of the allocation of the Special Allocation Fund is quite appropriate in closing the fiscal gap that has not been covered by the General Allocation Fund and Revenue Sharing Fund.…”
Section: Modelmentioning
confidence: 79%
See 1 more Smart Citation
“…Based on the test results, these findings are relevant to the study of [2] shows that the Special Allocation Fund has a positive and significant effect on the level of regional financial independence. This shows that the realization of the allocation of the Special Allocation Fund is quite appropriate in closing the fiscal gap that has not been covered by the General Allocation Fund and Revenue Sharing Fund.…”
Section: Modelmentioning
confidence: 79%
“…One of the goals of the government in implementing regional autonomy is to provide flexibility for regions to manage their own households in order to increase equitable development for people's welfare. The level of independence of a region can be seen from self-support in the financial sector related to regional revenue receipts that have been submitted by the center so that regions can carry out their regional activities independently [1] There are several indicators to measure the financial performance of local governments, one of which is the level of regional financial independence which indicates the potential of local governments to carry out local government work independently regarding development and service to the community [2]. The previous study from [3] showed factors that could affect the level of financial independence including the effectiveness of PAD, general allocation funds, special allocation funds and profit sharing funds.…”
Section: Introductionmentioning
confidence: 99%
“…Dalam penyelenggaraan pemerintahan, laporan keuangan harus bersifat transparan yaitu adanya pertanggungjawaban yang terbuka, adanya aksebilitas terhadap laporan keuangan, adanya publikasi laporan keuangan, hak untuk tahu hasil audit, dan adanya ketersediaan dalam infomasi kinerja (Mbipi et al, 2021). Salah satu prinsip dalam pengelolaan keuangan desa yaitu akuntabilitas.…”
Section: Hasil Dan Pembahasanunclassified
“…Kajian terhadap kinerja fiskal pemerintah daerah menjadi urgent, khususnya bagi penyusunan peraturan dan menilai manajemen pemda serta memastikan adanya dampak positif bagi kesejahteraan masyarakat (Hamid, 2018). Terdapat beberapa indikator yang dapat menjadi alat dalam mengukur performa finansial pemda, satu diantaranya tingkat kemandirian keuangannya, yang mengindikasikan potensi pemda dalam melaksanakan pekerjaan pemerintah daerah secara mandiri, pembangunan, dan pelayanan kepada masyarakat (Mbipi et al, 2021). Dengan demikian, mandirinya keuangan pemda terlihat di pos PAD pada laporan keuangan LRA-nya.…”
Section: Pendahuluanunclassified
“…Semakin besar proporsi PAD terhadap perndapatan daerah secara keseluruan, berarti kemandirian keuangan pemda tersebut semakin bagus (Putra & Hidayat, 2016). Terdapat empat pola hubungan tingkat kemandirian daerah, yaitu Instruktif, Konsultatif, Partisipatif, dan Delegatif (Mbipi et al, 2021). Besar kecilnya suatu daerah memperoleh pembayaran pajak dan retribusi oleh warga masyarakat berakibat pada kesanggupan pemerintah daerah dalam membiayai kepemerintahannya sendiri, misalnya pembangunan infrastruktur dan pelaksanaan pelayanan kepada masyarakat sehingga dapat diketahui seberapa besar tingkat kemandirian keuangan daerah.…”
Section: Kemandirian Keuanganunclassified